2014
DOI: 10.3109/09537104.2014.995613
|View full text |Cite
|
Sign up to set email alerts
|

The association between platelet count and metabolic syndrome in children and adolescents

Abstract: Higher platelet count was associated with increased prevalence and risk of MetS in children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
5
25
0
Order By: Relevance
“…19,20 Other platelet indices studied include platelet-tolymphocyte ratio, which was found to be elevated in MetS patients, as well as shown be a marker for cardiovascular dysfunction in MetS patients by Akboga et al 21,22 A large multicenter study based in South Korea, spanning 2 years from 2010 to 2012 and involving 2,228 patients by Lim et al, showed that elevated platelet indices were a risk stratification marker for development of MetS not only in adults but in the pediatric and adolescent population as well. 23 Similar results on proinflammatory biomarkers in MetS patients in the adolescent age group were documented by Can et al 24 On comparison with controls, Zaccardi et al found that MPV was significantly higher in patients with type 2 DM but not in MetS patients, findings similar to what were obtained in our study as well. 25,26…”
Section: Discussionsupporting
confidence: 92%
“…19,20 Other platelet indices studied include platelet-tolymphocyte ratio, which was found to be elevated in MetS patients, as well as shown be a marker for cardiovascular dysfunction in MetS patients by Akboga et al 21,22 A large multicenter study based in South Korea, spanning 2 years from 2010 to 2012 and involving 2,228 patients by Lim et al, showed that elevated platelet indices were a risk stratification marker for development of MetS not only in adults but in the pediatric and adolescent population as well. 23 Similar results on proinflammatory biomarkers in MetS patients in the adolescent age group were documented by Can et al 24 On comparison with controls, Zaccardi et al found that MPV was significantly higher in patients with type 2 DM but not in MetS patients, findings similar to what were obtained in our study as well. 25,26…”
Section: Discussionsupporting
confidence: 92%
“…3 Several studies have found that hematological parameters, including white blood cell (WBC), red blood cell (RBC) and platelet counts, platelet to lymphocyte ratio, neutrophil to lymphocyte ratio (NLR), lymphocyte-tomonocyte ratio (LMR), monocyte to high-density lipoprotein cholesterol (HDL-C) ratio (MHR) and lymphocyte to high-density lipoprotein ratio (LHR), may be related to MetS and the atherosclerotic process, as potential indicators of prothrombotic and proinflammatory states. [4][5][6][7][8] As known, HDL-C plays an important role in antiinflammatory, antioxidant and antithrombotic progress, and can inhibit cytokine-induced expression of endothelial cell adhesion molecules. 9,10 It was reported that the MHR was independently associated with coronary atherosclerosis in patients with stable coronary artery disease; 11 however, there is inconsistency in changes in the lymphocyte count in MetS patients.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 , 16 ] However, in another study, higher PLT count was associated with increased prevalence and risk of MS in both genders. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%